(untitled) (Proceedings of International Educators Conference, 2024)
This article describes some peculiarities of wealth distribution in in Islamic economics. It explains the stages of distribution and role and importance of income distribution for well-being of society members. The paper offers some more elements for proper distribution and redistribution process.